Qualitative study of socio-cultural challenges in the nursing profession in Pakistan - Sidra Abbas; Rubeena Zakar; Florian Fischer (BMC, 2020)
Abstract Background In a patriarchal social system, a women-dominated profession like nursing is mostly seen as a disempowered group due to its stereotypical image and negative connotations. The low social prestige of this profession is based on the roles typically assigned to men and women to maintain gender identity according to their performance and embodiment. The aim of this study was to explore the social and cultural challenges faced by nurses while creating their professional image within the regional context of Lahore (Punjab) in Pakistan. Methods A qualitative research design was chosen to conduct one-to-one, in-depth interviews with twelve nurses. Recruitment was based on purposive sampling from three large public hospitals in Lahore to learn about nurses' perceptions of social and cultural challenges in the nursing profession. A thematic analysis was conducted using the data analysis software package NVivo 12 Plus. Results Cultural values give preference for female nurses. We have identified four major themes related to the social and cultural challenges facing the nursing profession: 1) gender-segregated profession, 2) inappropriate portrayals by the media, 3) issues around marriage settlement, and 4) identity from a religious perspective. These conflicts are affecting the professional status and changing perceptions of nurses, who either do not choose to remain in the nursing profession or do not recommend nursing as a career option. These ongoing constraints are still perpetuating and increasing shortage of nurses within the Pakistani healthcare system. Conclusion The present study solely highlights nurses' perspectives on redefining gender roles and gender integration within the nursing profession. It argues that there is a need for positive portrayals in the media for the removal of public misperceptions related to nursing. This would reduce the shortage of nurses along with increasing retention and improving the quality of healthcare delivered to the public.